Strategy for Strengthening the Business Management of Joint BUM Desa/BUM Desa and its Business Units - ., Suamperi (KnE Social Sciences, 2022)
In the strategic program to strengthen the management of village-owned enterprises, the following steps are needed: the joint BUM Desa/BUM Desa data collection should be carried out by the Ministry based on the BUM Desa/BUM Desa registration data in the village information system. The data collection should at least include information on the following aspects: institutional, management, BUM Desa/BUM Desa together and/or BUM Desa/BUM Desa business units, cooperation or partnership, assets and capital, administration, financial reports, accountability, and advantages for the village and its community. The results of the data collection serve as the basis for the evaluation, guidance and development of BUM Desa/BUM Desa together. BUM Desa/BUM Desa jointly participate in data collection through the village information system. Provisions are made on administrative formats, financial reports, and accountability. The development of BUM Desa/BUMDes Bersama is carried out through the following strategies: institutional revitalization; improving the quality of management, administrative management, reporting and accountability; and strengthening the organization, management, cooperation and partnerships, asset management and capita, management of profits, and benefits for the village and its community. Keywords: strategy, strengthening, management, BUMDes